2021
DOI: 10.1038/s41598-021-83205-0
|View full text |Cite
|
Sign up to set email alerts
|

Parental educational status independently predicts the risk of prevalent hypertension in young adults

Abstract: Identification of individuals at risk of hypertension development based on socio-economic status have been inconclusive, due to variable definitions of low socio-economic status. We investigated whether educational status of individuals or their parents predicts prevalent hypertension in young adult population, by analyzing data of more than 37,000 non-institutionalized subjects from Korea National Health and Nutrition Examination Survey 2008 to 2017. Although low educational status of individual subjects was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…According to Dannefer and Huang Mgs (2017), cumulative risk experiences, in particular among those from relatively disadvantaged family backgrounds, impose important restrictions on youth’ sense of agency. For instance, unskilled parental occupations; unemployment; and retirement due to disability and older age (accompanied by significant financial difficulties) are factors that can impact youth’s choices (Guedes, 2015; Suh et al, 2021). Aware of their parents’ difficulties, adolescents tend to feel more inhibited to take risks and explore new paths.…”
Section: The Contribution Of Parental Meta-emotion and Attachment To ...mentioning
confidence: 99%
“…According to Dannefer and Huang Mgs (2017), cumulative risk experiences, in particular among those from relatively disadvantaged family backgrounds, impose important restrictions on youth’ sense of agency. For instance, unskilled parental occupations; unemployment; and retirement due to disability and older age (accompanied by significant financial difficulties) are factors that can impact youth’s choices (Guedes, 2015; Suh et al, 2021). Aware of their parents’ difficulties, adolescents tend to feel more inhibited to take risks and explore new paths.…”
Section: The Contribution Of Parental Meta-emotion and Attachment To ...mentioning
confidence: 99%
“…Some studies suggest that adverse life circumstances, such as low parental education, unskilled parental occupations, separation or divorce among parents, deaths of close relatives, and high residential mobility, can undermine individuals' development (Hitlin & Kirkpatrick Johnson, 2015;Spisma et al, 2015). Specifically, parents' low education and unskilled occupations have been associated with their children's health problems (Suh et al, 2021). Parental unemployment and retirement due to disability or older age, which are often accompanied by significant financial difficulties, have also been described as difficult situations that may impact the choices youth make (Guedes, 2015).…”
Section: Psychosocial Riskmentioning
confidence: 99%
“…Furthermore, higher SES was independently negatively associated with the spot urine Na/K ratio. Two previous studies in young people reported that the considered associations between SES and urinary electrolyte excretion in Australian children [16] and Korean young adults [33] were positively associated with urinary sodium. Although the item in this study was different from that of previous studies, the results of the current study in Japanese adolescent and child football players were consistent with these findings, suggesting that SES influences the urinary Na/K ratio even in adolescents.…”
Section: Association Between Ses and The Urinary Na/k Ratiomentioning
confidence: 89%